2022
DOI: 10.3389/fnmol.2022.826427
|View full text |Cite
|
Sign up to set email alerts
|

Loss of KCC2 in GABAergic Neurons Causes Seizures and an Imbalance of Cortical Interneurons

Abstract: K-Cl transporter KCC2 is an important regulator of neuronal development and neuronal function at maturity. Through its canonical transporter role, KCC2 maintains inhibitory responses mediated by γ-aminobutyric acid (GABA) type A receptors. During development, late onset of KCC2 transporter activity defines the period when depolarizing GABAergic signals promote a wealth of developmental processes. In addition to its transporter function, KCC2 directly interacts with a number of proteins to regulate dendritic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 112 publications
(163 reference statements)
5
9
0
Order By: Relevance
“…However, compared to the ipsilateral iml and the contralateral oml/mml, the fluorescence intensity in the ipsilateral oml/mml was reduced, suggesting that KCC2 is primarily lost from the denervated dendritic segments of the granule cells but not from the denervated dendrites of interneurons. Interestingly, a recent study showed that a selective permanent loss of KCC2 in interneurons leads to cortical seizures due to alterations in the distribution of interneuron subtypes ( Zavalin et al, 2022 ). That suggests that a granule cell-specific, transient reduction of KCC2 in the denervated dentate gyrus with preserved KCC2 in interneurons would not cause such a dramatic excitation-inhibition imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to the ipsilateral iml and the contralateral oml/mml, the fluorescence intensity in the ipsilateral oml/mml was reduced, suggesting that KCC2 is primarily lost from the denervated dendritic segments of the granule cells but not from the denervated dendrites of interneurons. Interestingly, a recent study showed that a selective permanent loss of KCC2 in interneurons leads to cortical seizures due to alterations in the distribution of interneuron subtypes ( Zavalin et al, 2022 ). That suggests that a granule cell-specific, transient reduction of KCC2 in the denervated dentate gyrus with preserved KCC2 in interneurons would not cause such a dramatic excitation-inhibition imbalance.…”
Section: Discussionmentioning
confidence: 99%
“… [ 150 ] KCC2 Mouse with conditional knockout of KCC2 in Dlx5-lineage neurons (Dlx5 KCC2 cKO) (in vivo) Electrophysiology Loss of KCC2 caused occasional spontaneous seizures. [ 159 ] KCC2 A mouse line with 2–3-fold KCC2 overexpression occurs in pyramidal neurons (in vivo) EEG d monitoring Adult Enhanced KCC2 expression increased diazepam’s efficacy in stopping EEG seizures. [ 160 ] Preventing KCC2- Thr906/Thr1007 phosphorylation Intraperitoneal injection of kainate in male KCC2-Thr906Ala/Thr1007Ala knock-in mice (in vivo) EEG monitoring Neonatal Prevention of Thr906 and Thr1007 phosphorylation delayed the onset and severity of kainate induced seizures.…”
Section: Posttranslational Regulatory Mechanisms Of Kcc2mentioning
confidence: 99%
“…Zavalin et al conducted a study where they conditionally knocked out KCC2 in Dlx5-lineage neurons (Dlx5 KCC2 cKO) in a mouse line, targeting cortical interneurons and post-mitotic GABAergic neurons in the forebrain during embryonic development. They found that the loss of KCC2 caused an imbalance in cortical interneuron subtypes, occasional spontaneous seizures, and early death [ 159 ]. Cheung et al established a mouse line with 2–3-fold KCC2 overexpression occurring in pyramidal neurons.…”
Section: Pharmacological Modulation Of Kcc2mentioning
confidence: 99%
“…122 Reduced expression of KCC2 disrupts the E/I balance causing brain dysfunction, including intractable epilepsy. [125][126][127][128][129] Indeed, KCC2 mutations that impair extrusion of Cl − humans result in severe seizures in mice and in humans [130][131][132] and are associated with schizophrenia and ASD. 130 Similarly, psychological stress and neuroinflammation during early prenatal development reduce KCC2 expression delaying the E/I GABA shift, which has been implicated in neurodevelopmental and psychiatric disorders.…”
Section: Potential Common Effectorsmentioning
confidence: 99%